2016
DOI: 10.1021/acsenergylett.6b00356
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorinated Alkoxyaluminate Electrolyte for Magnesium-Ion Batteries

Abstract: The lack of electrolytes that simultaneously possess high Coulombic efficiency, conductivity, and voltage stability has hindered the deployment of rechargeable magnesium-ion batteries. With few exceptions, the tenacious oxide layer on magnesium metal has limited the scope of research to halide ion-based electrolytes, which help activate the electrode surface but also limit the working voltage window considerably. Herein, we demonstrate a new class of magnesium electrolytes based on fluoroalkoxyaluminate anions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
139
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 46 publications
8
139
1
4
Order By: Relevance
“…Mg and astripping potential at Angewandte Chemie Zuschriften À0.111 V, giving overpotential of 197 mV,w hich is comparable with Mg/MgCl 2 /AlCl 3 (MMAC) electrolytes, [3f] but lower than reported chloride-free Mg electrolytes. Furthermore,t he Mg-FPB electrolyte exhibited an outstanding anodic stability at more than 4.0 Vv s. Mg, which is comparable with reported chloride-free Mg electrolytes, [4][5][6][7] but significantly improved over other reported Mg electrolytes. Furthermore,t he Mg-FPB electrolyte exhibited an outstanding anodic stability at more than 4.0 Vv s. Mg, which is comparable with reported chloride-free Mg electrolytes, [4][5][6][7] but significantly improved over other reported Mg electrolytes.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Mg and astripping potential at Angewandte Chemie Zuschriften À0.111 V, giving overpotential of 197 mV,w hich is comparable with Mg/MgCl 2 /AlCl 3 (MMAC) electrolytes, [3f] but lower than reported chloride-free Mg electrolytes. Furthermore,t he Mg-FPB electrolyte exhibited an outstanding anodic stability at more than 4.0 Vv s. Mg, which is comparable with reported chloride-free Mg electrolytes, [4][5][6][7] but significantly improved over other reported Mg electrolytes. Furthermore,t he Mg-FPB electrolyte exhibited an outstanding anodic stability at more than 4.0 Vv s. Mg, which is comparable with reported chloride-free Mg electrolytes, [4][5][6][7] but significantly improved over other reported Mg electrolytes.…”
supporting
confidence: 79%
“…[2] However,t he research into rechargeable Mg batteries is still in its infancy, and development of Mg batteries is primarily hampered by two grand challenges,t he lack of high performance Mg 2+ electrolyte [2b,c] and energy-dense cathode materials. [3] The reported Mg 2+ electrolytes applied in Mg batteries are mainly based on the combination of aMg-containing Lewis base (for example,Grignard reagents and MgCl 2 )and aLewis acid (for example,A lCl 3 [4] Mg(CB 11 H 11 F) 2, [5] Mg[Al-(HFIP) 4 ] 2 , [6] and Mg[B(HFIP) 4 ] 2 (HFIP =-OCH(CF 3 ) 2 ). [3] The reported Mg 2+ electrolytes applied in Mg batteries are mainly based on the combination of aMg-containing Lewis base (for example,Grignard reagents and MgCl 2 )and aLewis acid (for example,A lCl 3 [4] Mg(CB 11 H 11 F) 2, [5] Mg[Al-(HFIP) 4 ] 2 , [6] and Mg[B(HFIP) 4 ] 2 (HFIP =-OCH(CF 3 ) 2 ).…”
mentioning
confidence: 99%
“…[77] Recently, Arnold and co-workers reported that magnesium hexafluoroisopropylaluminate Mg[Al(hfip) 4 ) and conductivities (>6 mS/cm). [78] This conductive salt solution was synthesized via a three-step reaction. Firstly, both educts of magnesium fluoroalkoxide Mg(hfip) 2 and aluminumfluoroalkoxide Al(hfip) 3 need to be synthesized, followed by mixing them in DME.…”
Section: Electrolytes From Chloride-free Magnesium Saltsmentioning
confidence: 99%
“…Die oxidative Stabilitätb eträgt 5V gegen Mg (5.7 V gegen Li). [41] Diese Arbeit wurde auf die Synthese von Fluoralkoxyborat-Elektrolyten ausgedehnt, deren Herstellung in einem Schritt durch die Reaktion von Tr is(2H-hexafluorisopropyl)borat und Magnesiumfluorid in 1,2-Dimethoxyethan erfolgte. Die Kristallstruktur des Magnesiumtetraphenylaluminats ((Mg 2 (m-Cl) 3 ·6 THF)(AlPh 4 )), das das Magnesium-Dimer-Kation enthält, wird in Abbildung 2B gezeigt.…”
Section: In Situ Erzeugte Magnesium-elektrolyteunclassified